2021
DOI: 10.1038/s42005-021-00711-3
|View full text |Cite
|
Sign up to set email alerts
|

Optical detection of the susceptibility tensor in two-dimensional crystals

Abstract: The out-of-plane optical constants of monolayer two-dimensional materials have proven to be experimentally elusive. Owing to their reduced dimensionality, optical measurements have limited sensitivity to these properties which are hidden by the optical response of the substrate. Therefore, there remains an absence of scientific consensus on how to correctly model these crystals. Here we perform an experiment on the optical response of a single-layer two-dimensional crystal that addresses these problems. We suc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Therefore, the body resistance of the VFLG was independent of the substrates. Xu et al also reported that the substrate did not alter the intrinsic optical conductivity of a 2D crystal [32]. The field electron emission characterization of the VFLG on Si, stainless-steel and flexible carbon-cloth substrates were measured to further explore the influence of substrates on VFLG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the body resistance of the VFLG was independent of the substrates. Xu et al also reported that the substrate did not alter the intrinsic optical conductivity of a 2D crystal [32]. The field electron emission characterization of the VFLG on Si, stainless-steel and flexible carbon-cloth substrates were measured to further explore the influence of substrates on VFLG.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the body resistance of the VFLG was independent of the substrates. Xu et al also reported that the substrate did not alter the intrinsic optical conductivity of a 2D crystal [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Parameters of interest are extracted by a simultaneous fit of the model parameters to the Psi and Delta curves. Although the technique allows for optical characterization of a sample with thickness down to a monolayer, measurements of the anisotropic samples are challenging 36 and require thick samples to assure sufficient light interaction with in-plane and, especially, outof-plane polarization components to sense the anisotropy. That is particularly difficult for samples with a high refractive index what reduces greatly the angle of refraction and thus the amount of the out-of-plane components of the refracted beam in the sample.…”
Section: A Uniaxial Semiconductorsmentioning
confidence: 99%
“…Bi SeO is a layered material that was grown as a native oxide on the layered Bi O Se [ 41 ]; however, it remains unclear how it would be grown on other materials. Consequently, more research needs to be conducted, and delicate experimental methods should be employed to measure and verify the actual performance of the 2D vdW materials and their optical and dielectric properties [ 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%